Ontogeny and programming of the fetal temporal cortical endocannabinoid system by moderate maternal nutrient reduction in baboons (Papio spp.). Issue 6 (25th March 2019) - Gandhi, Kushal; Montoya‐Uribe, Vanessa; Martinez, Stacy; David, Samuel; Jain, Bobby; Shim, Grace; Li, Cun; Jenkins, Susan; Nathanielsz, Peter; Schlabritz‐Loutsevitch, Natalia
Abstract: Poor nutrition during pregnancy is a worldwide public health problem. Maternal nutrient reduction (MNR) is associated with maternal and fetal stress and a sex‐dependent decrease in nonhuman primate (NHP) cognitive performance. Early life stress potentiates epileptogenesis in a sex‐specific manner, and temporal lobe (TL) epilepsy is associated with neurocognitive disorders. The endogenous cannabinoid system (ECS) demonstrates remarkable developmental changes and plays a key role in aging‐related diseases (e.g., dementia). Baboons have been studied as a natural model of epilepsy and express all ECS system components. We therefore evaluated baboon fetal temporal cortex ECS ontogenic and MNR‐dependent changes. At 120 days gestational age (dGA) (term 185 days), maternal, fetal, and placental morphometry were similar between control and MNR pregnancies. MNR maternal weight gain was decreased compared with controls at 165 dGA independent of fetal sex. In male fetuses, expression of ECS synthesizing and degrading enzymes was gestational age‐dependent, with the exception of fatty acid amide hydrolase (FAAH). MNR had a sex‐specific effect on the protein expression of CB1R during development: CB1R protein expression was decreased in fetal temporal cortex of male fetuses at 120 and 140 dGA. Our data reveal that the MNR has sex‐specific effects on temporal cortical expression of the ECS in baboon offspring and shows vulnerability of ECS in male fetuses during gestation. Abstract : Maternal nutrient reduction (MNR) is associated with maternal and fetal stress and a sex‐dependent decrease in nonhuman primate (NHP) cognitive performance. The endogenous cannabinoid system (ECS) demonstrates remarkable developmental changes and plays a key role in aging‐related diseases. Baboons have been studied as a natural model of epilepsy and express all ECS system components; therefore, we evaluated baboon fetal temporal cortex ECS ontogenic and MNR‐dependent changes.